"Den som er godt forberedt, har ikke uflaks": norsk OL-deltakelse i Vancouver - risiko, forberedelse og resultater - Andersen, S. S.; Hanstad, D. V. (Scandinavian Sport Studies Forum, 2011)
In Norway, the central elite sport organization, Olympiatoppen, has the overall responsibility for coordinating and supporting all elite sport efforts. Part of this is the responsibility for the Norwegian participation in the Olympic Games. This study focuses on the 2010 Vancouver project, and how it was carried out in the light of the negative experiences form the 2006 Winter Olympics in Turin.